2017
DOI: 10.1039/c7ra07060h
|View full text |Cite
|
Sign up to set email alerts
|

New and bioactive natural products from an endophyte of Panax notoginseng

Abstract: Secondary metabolites with cytotoxic activity, antiviral activity and antimicrobial activity from the endophytic fungi of Panax notoginseng.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…The plant has been cultivated and domesticated for approximately 400 years, mainly in Yunnan and Guangxi provinces, China. Continuous cultivation of P. notoginseng in the same field will led it to be attacked vulnerably by various soil-borne pathogens, like fungi, bacteria and nematodes [ 9 ]. The rhizospheric and endophytic fungal communities are considered not only of vital importance for plant health and soil fertility, but also to have positive effects on plant resistance to diseases and insects.…”
Section: Introductionmentioning
confidence: 99%
“…The plant has been cultivated and domesticated for approximately 400 years, mainly in Yunnan and Guangxi provinces, China. Continuous cultivation of P. notoginseng in the same field will led it to be attacked vulnerably by various soil-borne pathogens, like fungi, bacteria and nematodes [ 9 ]. The rhizospheric and endophytic fungal communities are considered not only of vital importance for plant health and soil fertility, but also to have positive effects on plant resistance to diseases and insects.…”
Section: Introductionmentioning
confidence: 99%
“…tenuiussimum , P. janthinellum ) and four pathogens (bacteria: A. marplatensis, N. rhamnosiphila ; fungi: Cl. gossypicola, F. oxysporium ) from the rhizosphere soil of P. notoginseng were tested according to the methods of previous studies ( Xie et al., 2017 , Liu et al., 2010 , Zhang et al., 2004 ). At a concentration of 0.1 mg mL −1 , compounds 2 and 5 showed substantial antibacterial activity on Ba.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on rhizosphere microorganisms of P. notoginseng have mainly focused on the microbial community structure and the pathogenic effect of microorganisms on the plant ( Miao et al., 2015 , Guan et al., 2005 , Guan et al., 2006 , Guan et al., 2010 ). Only one study has reported the inhibitory effects of the secondary metabolites from endophytic fungi of P. notoginseng on other rhizosphere microorganisms ( Xie et al., 2017 ). In the present study, compounds 3 , 4 , 6 and 7 significantly inhibited the growth of probiotics and promoted the growth of pathogens, at a concentration of 0.1 mg mL −1 , indicating that they may be potential allelochemicals causing root-rot disease, and manifest as antagonists against probiotics in the rhizosphere soil of P. notoginseng.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 109 – 110 exhibited cytotoxic activity against the 293, HepG2, Huh7 and KB cell line with an ID 50 values from 0.024 to 0.62 µM. Further, studies of the cellular mechanism of compounds 109 – 110 showed that they arrested HepG2 cells at the S phase [ 61 ].…”
Section: Bioactive Compounds In Mangrove Plantsmentioning
confidence: 99%